(untitled) (Conferencea, 2023)
The article discusses the growing number of scientific trends in the world and their significance for humanities studies of social and cultural status, as well as moral norms. The author emphasizes the need to effectively combine practical achievements with new knowledge in science and notes the responsibility that scientists bear for the results they achieve. The article examines the ethics of responsibility and unity as a response to the problems that humanity faces in conditions of crisis development. The author calls for the formation of a new ethics based on simple and understandable principles that unite the spiritual, scientific and practical potential of human civilization. He also emphasizes the importance of understanding the interconnectedness of all elements of the Universe and the need to recognize the spiritual dimension as a fundamental principle of existence. The author believes that misunderstanding and failure to take into account the laws of spiritual unity lead to a violation of values and the self-destruction of civilization. He proposes the principle of responsibility and laws as the basis for new ethical criteria in the relationship between man, society and the Universe. The article also discusses the role of science as a productive force of society and its ability to make changes in the conditions of the surrounding world to improve the quality of life of all humanity. However, the author emphasizes the dilemma between scientism and anti-scientism and calls for overcoming polar worldviews. In conclusion, the article emphasizes the importance of understanding the laws of science and the behavior of scientists to fully understand the development of science and its impact on society.